Individual Variation in Sleep Quality and Duration Is Related to Cerebral Mu Opioid Receptor Binding Potential during Tonic Laboratory Pain in Healthy Subjects. Issue 12 (18th September 2013) - Campbell, Claudia M.; Bounds, Sara C.; Kuwabara, Hiroto; Edwards, Robert R.; Campbell, James N.; Haythornthwaite, Jennifer A.; Smith, Michael T.
Abstract Objective Although poor sleep is a consequence of pain, sleep disturbance reciprocally induces hyperalgesia and exacerbates clinical pain. Conceptual models of chronic pain implicate dysfunctional supraspinal pain processing mechanisms, mediated in part by endogenous opioid peptides. Our preliminary work indicates that sleep disruption impairs psychophysical measures of descending pain modulation, but few studies have investigated whether insufficient sleep may be associated with alterations in endogenous opioid systems. This preliminary, exploratory investigation sought to examine the relationship between sleep and functioning of the cerebral mu opioid system during the experience of pain in healthy participants. Subjects and Design Twelve healthy volunteers participated in a 90‐minute positron emission tomography imaging scan using [11C]Carfentanil, a mu opioid receptors agonist. During the session, pain responses to a 10% topical capsaicin cream were continuously rated on a 0–100 scale. Participants also completed the Pittsburgh Sleep Quality Index (PSQI). Results Poor sleep quality (PSQI) was positively and significantly associated with greater binding potential (BP) in regions within the frontal lobes. In addition, sleep duration was negatively associated with BP in these areas as well as the temporal lobe and anterior cingulate. Conclusions These findings suggest that poor sleep quality and short sleep duration are associated with endogenous opioid activity in these brain regions during the application of a noxious stimulus. Elucidating the role of the endogenous opioid system in mediating some of the associations between sleep and pain could significantly improve our understanding of the pathophysiology of chronic pain and might advance clinical practice by suggesting interventions that could buffer the adverse effects of poor sleep on pain.